Pertumbuhan Dan Produksi Beberapa Galur dan Varietas Tomat (Lycopersicum esculentum Mill.) di Dataran Rendah - Fieco Charvel; Jurnawaty Sjofjan; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
One of exfort to increase tomato productivity is considering the cultivation aspect and using high yield variety which can adapt finely on it recent invironment. The other ways to increase the productivity is though plant breeding whis is the aim is to find and create new variety from certain population. The research aim to get tomatoes genotype that have fine growth and productivity at the low land which eventually can be created as new variety. The research held for 5 months. The research arranged experimentally using Randomined Block Design (RBD) consist of 24 plant and 10 samples. Treatment are Ratna Variety, Intan Variety, IPB T3-8-10, IPB T57-3, IPB T65-6-2012 and IPB T30-4-4. Parameters are plant height, stim girth, fruith longth, flowering date, harvesting date, fruit girth, weight per fruit and total yield per plant. Result shows that genotype of IPB T3-8-10 and IPB T-30-44 Had yield better than Ratna variety and Intan. A highest total of fruit weight per plant on genotype IPB T3-8-10 (1144 g), IPB T3-44 (796 g), IPB T57-3 (734.6 g) and IPB T65-6-2012 (605.6 g). Keyword : Lycopersicum esculentum Mill.,Variety, Genotype, Growth